The frequency of urinary tract infection and subclinical bacteriuria in dogs with allergic dermatitis treated with oclacitinib: a prospective study. Issue 5 (17th May 2017) - Simpson, Andrew C.; Schissler, Jennifer R.; Rosychuk, Rod A.W.; Moore, A Russell
Abstract : Background: Oclacitinib is a selective Janus kinase inhibitor for the treatment of canine allergic pruritus and atopic dermatitis in dogs. Glucocorticoids and ciclosporin increase urinary tract infection (UTI) frequency in dogs with inflammatory skin disease. Objective: Prospective study to evaluate the frequency of UTI and subclinical bacteriuria in dogs with allergic dermatitis receiving oclacitinib. Methods: Client‐owned dogs ≥2 years of age with a history of allergic dermatitis without apparent history of urinary tract disease or predisposition to UTI were included. Prior to enrolment, urinalysis and quantitative urine culture were performed after a washout period of at least 14 days from systemic antimicrobial drugs and 28 days for ciclosporin and systemic glucocorticoids. Dogs received oclacitinib at labelled dosing for an intended period of 180–230 days with a follow‐up urinalysis and urine culture performed regardless of urinary tract signs. Systemic antimicrobial and immune‐modulating drugs were not administered during the study. Results: None of the 55 dogs in this study developed UTI while receiving oclacitinib based on follow‐up urinalysis and urine culture performed during a range of 58–280 days (mean 195 days). Two dogs developed self‐limiting abnormal urinary tract signs without urine culture or urinalysis findings consistent with UTI. Conclusions and clinical importance: These findings indicate that bacteriuria is not an expected adverse effect in dogs treated with oclacitinib without a prior history of UTI or predisposing condition during this treatment period. Therefore, routine urine culture is not indicated for such dogs in the absence of abnormal urinalysis or clinical signs of urinary tract disease. Abstract : Background – Oclacitinib is a selective Janus kinase inhibitor for the treatment of canine allergic pruritus and atopic dermatitis in dogs. Glucocorticoids and ciclosporin increase urinary tract infection (UTI) frequency in dogs with inflammatory skin disease.Objective – Prospective study to evaluate the frequency of UTI and subclinical bacteriuria in dogs with allergic dermatitis receiving oclacitinib.Conclusions and clinical importance –These findings indicate that bacteriuria is not an expected adverse effect in dogs treated with oclacitinib without a prior history of UTI or predisposing condition during this treatment period. Therefore, routine urine culture is not indicated for such dogs in the absence of abnormal urinalysis or clinical signs of urinary tract disease.